Use of fermented Chinese medicine residues as a feed additive and effects on growth performance, meat quality, and intestinal health of broilers - Zhou, Xinhong; Li, Shiyi; Jiang, Yilong; Deng, Jicheng; Yang, Chuanpeng; Kang, Lijuan; Zhang, Huaidan; Chen, Xianxin (Frontiers in Veterinary Science, 2023)
Introduction The purpose of this research was to investigate how dietary supplementation with fermented herbal residues (FCMR) affected birds' development capacity, quality of meat, gut barrier, and cecum microbiota. Methods 540 cyan-shank partridge birds aged 47 days were chosen and divided into two groups of six replicates each and 45 birds for each replicate. The control group (CON) received a basal diet, while the trial group decreased a basic diet containing 5% FCMR. Results and discussion The findings revealed that the addition of FCMR decreased FCR and increased ADG in broilers (P < 0.05). Adding FCMR increased steaming loss in broiler chicken breasts (p < 0.05). Supplementation with FCMR significantly enhanced VH/CD and VH in the bird's intestine (jejunum, duodenum, and ileum) (p < 0.05). In addition, the addition of FCMR significantly down-regulated mRNA expression of INF-γ, IL-6, IL-1β, and TNF-α and up-regulated mRNA expression of ZO-1, Occludin, and Claudin (P < 0.05). Microbial 16S rDNA high-throughput sequencing study revealed that supplements with FCMR modified the cecum microbiota, and α-diversity analysis showed that supplementation with FCMR reduced the cecum bacterial abundance in broilers (P < 0.05). At the phylum level, the relative abundance of Spirochaetota increased considerably following FCMR supplementation (P < 0.05). The broiler cecum's close lot of Prevotellaceae_UCG-001 (P < 0.05), Desulfovibrio, Muribaculaceae, and Fusobacterium (p < 0.05) reduced when FCMR was supplemented. Supplementation with FCMR can promote growth capacity and maintain intestinal health in birds by enhancing gut barrier function and modulating the inflammatory response and microbial composition.